Experimental Study of Maritime Ships Corrosion in the Black Sea, by using MAG-M Mechanized Butt Welding with Metal-Cored Wire and Rutile Flux-Cored Wire (Geo-Eco-Marina, 2019)
In this paper we analyze the corrosion behavior of the MAG-M mechanized butt welding with metal-cored wire and rutile flux-cored wire at two welding positions PA and PC at in situ conditions of the Black Sea. The following materials were used in this experimental programme: base material (high strength steel sheet EH 36, dimensions 300 x 150 x 10 mm), filler material (metal cored wire (E70C6MH4) and rutile flux-cored wire (E71T1MH4) according to AWS A5.18, diameter 1.2 mm) and auxiliary materials (M21- Corgon 18 gas mixture and flat concave channel ceramic support). The samples were immersed in sea water harvested in the Black Sea and then subjected to corrosion tests by electrochemical methods.
Keywords: MAG-M welding; metal-cored wire; rutile flux-cored wire; marine corrosion